(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Due to the multiplicity of the implementation, virtual garment simulation requires the capacity of dressing a sewn garment onto various posed human models in a real time. In this paper, a three-step method has been proposed to accelerate the dress-up procedure. The virtual garment is first dressed onto a human model in a standing pose to record a distance map between the garment shell and the human model. And then the distance map is employed to generate a coarse match when the pose of the human model has been changed. Finally, a fine-tuned 3D configuration without surface penetration is generated after a draping/relaxation scheme. Experimental results suggest this method is a useful and fast treatment for dressing sewn virtual garment on various posed human models.